2022
DOI: 10.1159/000525014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Kangaroo Care on Premature Infants’ Oxygenation: Systematic Review

Abstract: <b><i>Introduction:</i></b> Kangaroo care (KC) is defined by the World Health Organization as a method of care consisting in putting premature infants or newborns in skin-to-skin contact with their parents. KC is an effective method of promoting health and well-being of infants and their families. Physiological stability during KC has been widely analyzed, however with controversial results. <b><i>Methods:</i></b> A systematic review was conducted. Electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The parameters studied included heart rate, SpO 2 , regional cerebral oxygen saturation and fractional oxygen extraction. This analysis of 25 studies on preterm infants noted no significant differences in the above parameters 27. However, studies that included regional cerebral oxygen saturation and fractional oxygen extraction showed a significant increase in the former but statistically non-significant differences in the latter 13 34 Online supplemental table 1.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The parameters studied included heart rate, SpO 2 , regional cerebral oxygen saturation and fractional oxygen extraction. This analysis of 25 studies on preterm infants noted no significant differences in the above parameters 27. However, studies that included regional cerebral oxygen saturation and fractional oxygen extraction showed a significant increase in the former but statistically non-significant differences in the latter 13 34 Online supplemental table 1.…”
Section: Discussionmentioning
confidence: 88%
“…Most of the published data were non-continuous (a manual count of events) rather than a continuous recording and focused on more mature (>32 weeks GA), self-ventilating infants. A recent systematic review noted that in stable preterm infants whether or not on respiratory support, no significant differences in heart rate, SpO 2 or fractional oxygen extraction were noted while regional cerebral oxygen saturation remained stable during KMC with a slight upward trend 27. A subsequent single centre study noted higher cerebral oxygenation and lower tissue oxygen extraction during KMC 28.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase continued even after receiving KC compared to before. Other researches also showed that the SpO 2 was significantly higher and more stable in newborns under KC than the newborns put in the incubator [ 8 , 26 ]. The results reported by Bera et al showed that the SpO 2 levels increased during and after KC, so the newborns’ need for oxygen supplementation decreased 15 min after the start of KC [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have shown an increase in the number of hypoxic and bradycardic events during KC [9, 15]. Recently, in a systematic review no evidence of clinically relevant effects on physiological monitoring parameters during KC was reported [16]. Furthermore, to the best of our knowledge, only five studies have analyzed fractional tissue oxygen extraction (FtOE) fraction during KC and in none of them significant differences in FtOE between KC and incubator care have been reported.…”
Section: Introductionmentioning
confidence: 99%